LOCAL BUDGETS IN WARTIME: OPPORTUNITIES FOR COOPERATION BETWEEN THE STATE AND SOCIAL INSTITUTIONS - BURNIAK, Ivan; KHODAN, Maksym (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The full-scale war in Ukraine has fundamentally transformed the structure, functions, and priorities of local budgets, forcing municipalities to shift resources from development programs toward the maintenance of basic services, humanitarian aid, and defense-related expenditures. This article examines the adaptive capacity of local budget systems under martial law and explores the potential for cooperation between public authorities and social institutions to enhance transparency, legitimacy, and fiscal sustainability. Drawing on comparative and analytical-descriptive methods, the research integrates data on public trust, international practices of participatory budgeting, and Ukraine’s experience in digital fiscal governance. It argues that declining trust in political institutions and the simultaneous rise of confidence in the Armed Forces, volunteer organizations, churches, and NGOs create new opportunities for collaborative governance and shared responsibility in managing local finances. The study introduces the concept of a «wartime architecture of participation», which institutionalizes the involvement of social institutions in budget allocation and decision-making. This model promotes accountability, reduces corruption risks, and strengthens social cohesion through inclusive mechanisms such as advisory budget councils, municipal trust funds, and participatory financing programs. Empirical examples, including the digital platform DREAM and participatory budgeting in Ivano-Frankivsk, illustrate how transparency and civic engagement can restore public confidence and improve fiscal resilience. The article concludes that wartime fiscal governance must rely not only on financial capacity but also on institutional trust, civic partnership, and adaptive management. Strengthening the synergy between the state and social institutions is therefore a key prerequisite for effective post-war recovery and sustainable territorial development.
Keywords: local budgets; martial law; civil society; trust; social institutions; participatory budgeting; transparency; fiscal resilience; Ukraine